PERAN WORLD HEALTH ORGANIZATION (WHO) DALAM UPAYA PENANGANAN HIV/AIDS DI INDONESIA TAHUN 2010-2013 - Monalisa Putri; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
This reseach describes the role of the World Health organization in haldling the spread of the HIV / AIDS outbreak in Indonesia. the rapid rise of HIV/AIDS cases in Indonesia, until 2013. The World Health Organization has declared an emergency on the international health situasion HIV / AIDS outbreak in Indonesia with the implementation of the program of the World Health Organization Global Programme on AIDS. Based on these issues, the problem is formulated as follows: